Does Setting Goals and Incentivizing Results Matter for the Psychosocial Work Environment?. Issue 4 (2nd October 2018) - Opstrup, Niels; Pihl-Thingvad, Signe
Abstract: This study investigates how central features of performance management, setting goals and incentivizing results, relate to the employees' satisfaction with the psychosocial work environment. Using data from 64 Danish university departments, including 2, 115 nested researchers, we find that having clear organizational goals is associated with higher levels of satisfaction with the psychosocial work environment. We also find that there is a positive relationship between the use of financial rewards and satisfaction with the psychosocial work environment, if there is a fit with the employees' extrinsic motivation structure. On the other hand, the use of sanctions is negatively correlated with the psychosocial work environment.